Study of the developing flow in a circular pipe with or without rotation - Gooi, Boon Chong. (2009)
Navier Stoke equations and energy equation involving steady, incompressible laminar flow in the developing region of a circular pipe without and with axial rotation were computed numerically using successive over relaxation algorithm incorporated with upwind first order differencing for the non linear advective terms and second order differencing for the high order derivatives to ensure diagonal dominance of the coefficient matrix.